2003
DOI: 10.1007/s00122-003-1466-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and molecular mapping of maize (Zea mays L.) stalk rot resistant gene Rfg1

Abstract: One single pathogen Fusarium graminearum Schw. was inoculated to maize inbred lines 1,145 (Resistant) and Y331 (Susceptive), and their progenies of F(1), F(2) and BC(1)F(1) populations. Field statistical data revealed that all of the F(1) individuals were resistant to the disease and that the ratio of resistant plants to susceptive plants was 3:1 in the F(2) population, and 1:1 in the BC(1)F(1 )population. The results revealed that a single dominant gene controls the resistance to F. graminearum Schw. The resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 12 publications
(11 reference statements)
0
15
0
1
Order By: Relevance
“…Relationship between QTLs and dominant resistance to maize stalk rot It is interesting that the dominant genes for resistance to maize stalk rot cauded by P. inflatum (Rpi1) and C. graminearum (Rfg1) reported by us (Yang et al 2004, and this paper) are located on chromosomes 6 and 4, respectively. Their map positions overlap with QTLs reported by Pe et al (1993).…”
Section: Genetic Analysis and Mapping Of The Rpi1 Genementioning
confidence: 92%
See 1 more Smart Citation
“…Relationship between QTLs and dominant resistance to maize stalk rot It is interesting that the dominant genes for resistance to maize stalk rot cauded by P. inflatum (Rpi1) and C. graminearum (Rfg1) reported by us (Yang et al 2004, and this paper) are located on chromosomes 6 and 4, respectively. Their map positions overlap with QTLs reported by Pe et al (1993).…”
Section: Genetic Analysis and Mapping Of The Rpi1 Genementioning
confidence: 92%
“…Meanwhile, we have analyzed resistance in a segregating population developed following singlepathogen inoculation with Fusarium graminearum Schw., and found that the resistance to this pathogen was controlled by a single dominant gene (Yang et al 2002b). Later, the resistance gene Rfg1 (resistance to F. graminearum Schw) was tagged and mapped to chromosome 6 (Yang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…QTLs conferring resistance to F. graminearum have been mapped on chromosomes 1, 3, 4, 5, 6, and 10 (Pe et al 1993;Yang et al 2004Yang et al , 2010a. A major QTL qRfg1, located in bin 10.04, was delimited into an interval of 500 kb ); while, a minor QTL, qRfg2, has been fine-mapped into a 300 kb interval with a putative candidate gene coding for an auxin-regulated protein (Zhang et al 2012).…”
Section: Genes Conferring Resistance To Biotic Stresses In Maizementioning
confidence: 99%
“…Yang et al (2004) utilizaram 820 marcadores e progênies F1 e F2 para o mapeamento de um gene de resistência em milho; em cevada, foram necessários 186 "primers" e a análise de 140 linhagens para a identificação de genes de resistência por BSA (Kutcher et al, 1996). No entanto, o presente trabalho demonstra que a BSA tem grande utilidade em programas de melhoramento genético de espécies florestais, e em especial do eucalipto, pois, com um grupo inicial de 20 indivíduos (os "bulks") e algumas dezenas de "primers" RAPD, já puderam ser localizados marcadores relacionados ao florescimento precoce.…”
Section: "Bulked Segregant Analysis" (Bsa) No Melhoramento Florestalunclassified